Therapeutic potential of hydrogen sulfide in osteoarthritis development - Song, Yunjia; Wu, Siyu; Zhang, Rong; Zhong, Qing; Zhang, Xuanming; Sun, Xutao (Frontiers in Pharmacology, 2024)
The pathological mechanisms and treatments of osteoarthritis (OA) are critical topics in medical research. This paper reviews the regulatory mechanisms of hydrogen sulfide (H2S) in OA and the therapeutic potential of H2S donors. The review highlights the importance of changes in the endogenous H2S pathway in OA development and systematically elaborates on the role of H2S as a third gaseous transmitter that regulates inflammation, oxidative stress, and pain associated with OA. It also explains how H2S can lessen bone and joint inflammation by inhibiting leukocyte adhesion and migration, reducing pro-inflammatory mediators, and impeding the activation of key inflammatory pathways such as nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK). Additionally, H2S is shown to mitigate mitochondrial dysfunction and endoplasmic reticulum stress, and to modulate Nrf2, NF-κB, PI3K/Akt, and MAPK pathways, thereby decreasing oxidative stress-induced chondrocyte apoptosis. Moreover, H2S alleviates bone and joint pain through the activation of Kv7, K-ATP, and Nrf2/HO-1-NQO1 pathways. Recent developments have produced a variety of H2S donors, including sustained-release H2S donors, natural H2S donors, and synthetic H2S donors. Understanding the role of H2S in OA can lead to the discovery of new therapeutic targets, while innovative H2S donors offer promising new treatments for patients with OA.